2009
DOI: 10.1007/s00442-009-1457-z
|View full text |Cite
|
Sign up to set email alerts
|

Reduced dispersal propensity in the wingless waterstrider Aquarius najas in a highly fragmented landscape

Abstract: Dispersal behaviour of animals in fragmented habitats has generated intensive theoretical attention but empirical data on the evolution of dispersal are still relatively scarce. Theory predicts reduced dispersal propensity in small and isolated habitat patches. We tested these predictions in the waterstrider Aquarius najas, a wingless species with special habitat demands. Flightlessness constrains insect dispersal and as a stream specialist A. najas cannot survive on still water. Lakes therefore represent a di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 54 publications
1
14
0
Order By: Relevance
“…According to Roff and Fairbairn (2007), dispersal may be a risky strategy, especially for species that inhabit very isolated habitat patches (Ahlroth et al, 2010), such as M. brachyptera (Poniatowski & Fartmann, 2010). With increasing isolation, the probability of failing to find a suitable habitat increases, which presumably results in a decrease in the survival rate of dispersing individuals (Harrison, 1980).…”
Section: Resultsmentioning
confidence: 99%
“…According to Roff and Fairbairn (2007), dispersal may be a risky strategy, especially for species that inhabit very isolated habitat patches (Ahlroth et al, 2010), such as M. brachyptera (Poniatowski & Fartmann, 2010). With increasing isolation, the probability of failing to find a suitable habitat increases, which presumably results in a decrease in the survival rate of dispersing individuals (Harrison, 1980).…”
Section: Resultsmentioning
confidence: 99%
“…Yet, if retention is partially the result of active behaviors and larval traits, then so might dispersal, depending on the situation. The propensity of individuals toward dispersal in several terrestrial species was shown to be genetically inherited (Haag et al 2005;Ahlroth et al 2010;Bitume et al 2011) or maternally induced (Tschirren et al 2007), according to local environmental conditions. The tendency of marine larvae to return to the natal patch or disperse might accordingly evolve as a function of increased habitat patchiness (Baskett et al 2007) or local conditions (Bowler and Benton 2011).…”
Section: Patterns Of Local Retentionmentioning
confidence: 99%
“…Intuitively, the first prediction from theory is that reduced dispersal should be selected for in fragmented landscapes due to the increased costs and risks of moving across fragmented landscapes (Olivieri andGouyon 1997, Travis andDytham 1999), and indeed this is often found in empirical studies. Reduced dispersal propensity and distance moved have been reported when fragmentation increases, due to increased inter-habitat distances or reduced matrix permeability (Dempster 1991, Lens and Dhondt 1994, Diffendorfer et al 1995, Matthysen and Currie 1996, Haddad 1999, Debinski and Holt 2000, Mennechez et al 2003, Schooley and Wiens 2004, Bonte et al 2006, Smith and Batzli 2006, Matter 2006, Cheptou et al 2008, Bowler and Benton 2009, Ahlroth et al 2010, Bergerot et al 2012, Eycott et al 2012, Banks and Lindenmayer 2014.…”
Section: Direct Effects Of Fragmentation Featuresmentioning
confidence: 99%